Implementasi Pembelajaran Berbasis Kemaritiman dalam Pembelajaran Anak Usia Dini Bagi Guru Kelompok Bermain di Kabupaten Lamongan - Lestari, Gunarti Dwi; Yulianingsih, Wiwin; Widodo; Yusuf, Ali; Rosyanafi, Rofik Jalal (DEDICATE: Journal of Community Engagement in Education, 2022)
Learning in early childhood is a structured combination that includes human elements, materials, facilities, equipment, and procedures that influence each other in achieving learning objectives. In essence, early childhood education presents the concept of learning while playing. Learning in early childhood is ’dependent’ on the teacher, it is hoped that teachers can develop maritime-based learning following the characteristics of the Lamongan district (Lina, 2021). By analyzing some of the problems above, the PKM Team will conduct a mentoring program for Playgroup teachers in Lamongan Regency to develop maritime-based learning. The PKM programs provided include program assistance, FGD (Focus Group Discussion), and brainstorming consisting of; (1) assistance in increasing the professionalism of Playgroup teachers in developing learning, (2) increasing the knowledge of Playgroup teachers related to maritime-based learning.